(untitled) (BULLETIN OF TARAS SHEVCHENKO NATIONAL UNIVERSITY OF KYIV. ORIENTAL LANGUAGES AND LITERATURES, 2023)
The publication presents the Ukrainian translation of the short story by the Thai writer of Chinese origin Nian Lamei "Girl with a floral garland". This work was translated into Ukrainian for the first time.